1982
DOI: 10.1530/acta.0.1010464
|View full text |Cite
|
Sign up to set email alerts
|

The pituitary-testicular axis of uraemic subjects on haemodialysis and continuous ambulatory peritoneal dialysis

Abstract: Pituitary-testicular function was evaluated in 18 patients with chronic renal failure, 9 treated by maintenance haemodialysis (HD) and 9 by continuous ambulatory peritoneal dialysis (CAPD), and compared with a non-uraemic control group. Serum total testosterone and the free testosterone index were significantly low in both dialysis groups. Basal FSH and LH levels were elevated but this reached significance only with regard to LH. The responses of both FSH and LH to the iv administration of LRH were normal. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1
2

Year Published

1983
1983
2003
2003

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 11 publications
0
7
1
2
Order By: Relevance
“…Essas alterações hormonais não se modificam nas fases finais da IRC, ou seja, antes, nas fases iniciais ou após anos de diálise 27,21,28,24 , embora algumas mulheres voltem a menstruar após o início da terapêutica dialítica 29,5,30 . O tipo de diálise (hemodiálise versus diálise peritoneal ambulatorial contínua) não interfere no padrão hormonal 31 , assim como os níveis dos diferentes hormônios não mostram diferenças significantes antes e depois da sessão de hemodiálise 26,32 . No Grupo I, das pacientes que menstruam regularmente, as dosagens de FSH e LH encontravam-se dentro da faixa da normalidade, com exceção de uma única paciente com níveis baixos, a saber, 0,91 e 0,8 mUI/ ml.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Essas alterações hormonais não se modificam nas fases finais da IRC, ou seja, antes, nas fases iniciais ou após anos de diálise 27,21,28,24 , embora algumas mulheres voltem a menstruar após o início da terapêutica dialítica 29,5,30 . O tipo de diálise (hemodiálise versus diálise peritoneal ambulatorial contínua) não interfere no padrão hormonal 31 , assim como os níveis dos diferentes hormônios não mostram diferenças significantes antes e depois da sessão de hemodiálise 26,32 . No Grupo I, das pacientes que menstruam regularmente, as dosagens de FSH e LH encontravam-se dentro da faixa da normalidade, com exceção de uma única paciente com níveis baixos, a saber, 0,91 e 0,8 mUI/ ml.…”
Section: Discussionunclassified
“…Esse fato poderia explicar os níveis baixos de FSH, por um efeito de bloqueio do eixo hipotálamo-hipofisário determinado pelo contraceptivo. Neste grupo, houve concordância com a maior parte da literatura no tocante às dosagens de FSH, que se mostram dentro da normalidade; nas dosagens de LH, embora muitos autores relatem níveis elevados 26,23,31,36,37 , não encontramos nenhum valor acima do considerado normal. Também aqui houve uma paciente com níveis ligeiramente diminuídos: trata-se de portadora de lúpus eritematoso sistêmico submetida a corticoterapia crônica com prednisona.…”
Section: Discussionunclassified
“…Altogether, these data confirm the presence of hypergonadotropic hypogonadism, a well-known hor monal dysfunction reported both in hemodialysis [3, 5, 9, 34. 35] and in peritoneal dialysis [ 14,36] patients. On the other hand, this group of uremic patients exhibited mod erately increased levels of prolactin, a factor that has been implicated in sexual dysfunction accompanying chronic renal failure [37][38][39], However, the results of thyroid function tests showed that all patients were euthyroid.…”
Section: Discussionmentioning
confidence: 99%
“…Both serum testos terone levels and the free testosterone index are decreased in men with chronic renal fail ure treated by hemodialysis or CAPD [30]. Plasma levels of luteinizing hormone and follicle-stimulating hormone are increased in men undergoing CAPD.…”
Section: Reproductive Functionmentioning
confidence: 99%